Religion and literacies in higher education: scoping the possibilities for faith-based meaning making - Smith, Paul Vincent (Critical Studies in Teaching and Learning, 2023)
Academic literacies  pursues  a  transformative  agenda,  which  involves ‘exploring  alternative ways  of  meaning  making  in  academia,  not  least  by  considering  the  resources  that  (student) writers bring to the academy as legitimate tools for meaning making’(Lillis andScott,2007: 13).  How  we  select  what  the  legitimate  tools  for  meaning  making  are  is  assumed  in  these studies,  but  not  established.  Given  the  generally  fraught  status  of  religion  in  the  academy,  a perspicuous  instance  of  this  problem  resides  in  the  question  of whether  religious  faith constitutes a ‘legitimate tool for meaning making’. We therefore need to think about how we establish  what  can  and  cannot  be  said  to  be legitimate  tools, and  whether  this  should  be decided  as  a  matter  of  normative  principle,  or  whether  it  can  be  arrived  at  empirically. Further, we would need to consider how such questions are to be properly incorporated into learning  and  assessment.  This  article  uses  qualitative  data  from  studies  into  religion  and higher education to provide some initial thoughts on how these questions could be addressed. It  carries  out  a  scoping  exercise  that  sheds  light  on  the  possibilities  of  the  employment  of religious identity in academic writing. It concludes that religious ideas and identities may on occasion be relevant without implying a threat to disciplinary rigour.